Bioactive compounds content of Snake Fruit Peel, Aloe Vera, and Stevia Extracts as Raw Material of Functional Drinks - Khairi, Amalya Nurul; Nurkhasanah, Nurkhasanah (Universitas Ahmad Dahlan, 2020)
The objective of the research is to analyze the content of the bioactive compounds of extracts made of snake fruit skin, Aloe vera, and Stevia as materials to make functional drinks. Salacca zalacca (Gaert.) Voss. cultivar has flavonoid, tannin, and a bit of alkaloid on its fruit peel. Aloe vera and Stevia also known to have antioxidant compounds. Aloe vera controls the metabolism of carbohydrates and maintaining homeostasis of glucose. The research methods are divided into steps: 1) the extraction of Snake fruit peel, Aloe vera, and Stevia; 2) the formulation of the functional drink; 3)the evaluation of antioxidant, total phenol, and tannin levels of the formulated extracts. The research used Randomized Group Design (RGD) of two factors, and each factor consists of 4 levels and 2 levels. Factor I=the ratio of snake fruit peel:Aloe vera extract (10:90 (v/v); 30:70 (v/v); 70:30 (v/v); 90:10 (v/v)) and factor II= addition of Stevia filtrate (2%; 4%) (v/v total). The best nutrient of the formulated functional drink is obtained by the composition of 90% snake fruit peel extract, 10% aloe vera, and 4% stevia. The snake fruit peel extract significantly affects the antioxidant activity and total phenol composition, aloe vera extract has an insignificant effect on active compounds, and stevia affects the tannin level of the functional drink.